What affects rural households’ entrepreneurial performance: Formal or informal finance availability? - Zhilue Xiang; Qiaoyue Yin; Xizhi Xue; Wanting Zhang; Xia Wang (PLoS ONE, 2026)
This study explores the role of financial availability in the growth and development of rural household entrepreneurship, particularly beyond the start-up phase. Focusing on entrepreneurial rural households, the study uses CFPS data to determine how financial availability influences their performance. Results reveal that formal finance significantly contributes to the growth of entrepreneurial performance, whereas informal finance does not. Further, the positive impact of formal finance exhibits notable regional heterogeneity. These findings suggest policies should strengthen formal finance, adopt regionally differentiated support strategies, and guide the complementary development of informal finance to foster sustainable rural entrepreneurship growth.